Grapevine: A profile‐based exploratory search and recommendation system for finding research advisors. Issue 1 (22nd October 2020) - Rahdari, Behnam; Brusilovsky, Peter; Babichenko, Dmitriy; Littleton, Eliza Beth; Patel, Ravi; Fawcett, Jaime; Blum, Zara
Abstract: Finding research advisors is an important and challenging task for college students. On one hand, a research advisor that matches student interests and past preparation could fully engage the student with an exciting and productive research experience. On the other hand, students are frequently unable to formulate their interests and experience in a way that allows them to independently find the most compatible advisors using search and browsing tools. This paper reports our experience with designing and evaluating Grapevine, an exploratory search and recommender system aimed at helping students, especially those less prepared and underrepresented in certain fields, find research advisors.